Secondary White Matter Injury Mediated by Neuroinflammation after Intracerebral Hemorrhage and Promising Therapeutic Strategies of Targeting the NLRP3 Inflammasome - Xiao, Linglong; Wang, Mengqi; Shi, Yifeng; Xu, Yangyang; Gao, Yuan; Zhang, Wei; Wu, Yang; Deng, Hao; Pan, Wei; Wang, Wei; Sun, Haitao (Current Neuropharmacology, 2023)
Intracerebral hemorrhage (ICH) is a neurological disease with high mortality and disability. Recent studies showed that white matter injury (WMI) plays an important role in motor dysfunction after ICH. WMI includes WMI proximal to the lesion and WMI distal to the lesion, such as corticospinal tract injury located at the cervical enlargement of the spinal cord after ICH. Previous studies have tended to focus only on gray matter (GM) injury after ICH, and fewer studies have paid attention to WMI, which may be one of the reasons for the poor outcome of previous drug treatments. Microglia and astrocyte-mediated neuroinflammation are significant mechanisms responsible for secondary WMI following ICH. The NOD-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome activation, has been shown to exacerbate neuroinflammation and brain injury after ICH. Moreover, NLRP3 inflammasome is activated in microglia and astrocytes and exerts a vital role in microglia and astrocytes-mediated neuroinflammation. We speculate that NLRP3 inflammasome activation is closely related to the polarization of microglia and astrocytes and that NLRP3 inflammasome activation may exacerbate WMI by polarizing microglia and astrocytes to the pro-inflammatory phenotype after ICH, while NLRP3 inflammasome inhibition may attenuate WMI by polarizing microglia and astrocytes to the anti-inflammatory phenotype following ICH. Therefore, NLRP3 inflammasome may act as leveraged regulatory fulcrums for microglia and astrocytes polarization to modulate WMI and WM repair after ICH. This review summarized the possible mechanisms by which neuroinflammation mediated by NLRP3 inflammasome exacerbates secondary WMI after ICH and discussed the potential therapeutic targets.
Keywords: secondary white matter injury